Livelihood vulnerability and climate change: a comparative analysis of smallholders in the Indo-Gangetic plains - Terese E. Venus; Stephanie Bilgram; Johannes Sauer; Arun Khatri-Chettri (Environment, Development and Sustainability, 2021)
In the Indo-Gangetic Plains, one of India's most productive agricultural regions, smallholder livelihood vulnerability can inhibit sustainable development. As there are significant differences in economic development, natural resources and agricultural productivity within the region, we estimate the Livelihood Vulnerability Index in two districts (Vaishali, Bihar and Karnal, Haryana) to determine suitable adaptation strategies under diverse conditions. To reflect different aspects of climate exposure, we include both self-reported climate shocks and spatially interpolated weather data. The assessment of 1127 households shows that while both districts have similar exposure and adaptive capacity levels, the sensitivity dimension makes Vaishali more vulnerable to climate change. To reduce sensitivity, decision-makers should focus on improving infrastructure (e.g., permanent housing, latrines, health centers, alternative energy sources). To improve adaptive capacity and reduce climate risk in both regions, policymakers should promote the expansion of extension training for livelihood diversification, information and communication technologies as well as conservation agriculture.
Keywords: 330; Climate change; Livelihood~vulnerability; India; Smallholders